REFORMASI PELAYANAN MEDIK DASAR DI KABUPATEN SUMEDANG (STUDI KASUS PUSKESMAS PAMULIHAN KABUPATEN SUMEDANG) - Lalas Sulastri (Journal Of Regional Public Administration (JRPA), 2016)
This study aims to find out the reform of the basic medical services, barriers and measures taken to overcome obstacles in the implementation of the reform of the basic medical services at the health center Pamulihan Sumedang District. The method used is a qualitative research method. Data collection procedures used by the author is using the procedure of interview, observation, documentation and equipped with literature studies. Based on the survey results revealed that, the implementation of the reform of the basic medical service has not been implemented properly, the fact of budgetary support for infrastructure improvement of public services is very low, problems related to information services, assessment of competence has not been implemented fully for the staff. Barriers faced, namely the organizational culture is not conducive, each unit of service has not had a standard SOP. Efforts are being made, which makes the service flow chart and implement informed through public media complaints as the evaluation of the performance of services.